Modern green chemistry and heterocyclic compounds : molecular design, synthesis, and biological evaluation - Shinde, Ravindra S., 1979-; Haghi, A. K. (Burlington, ON, Canada ; Palm Bay, Florida, USA : Apple Academic Press, Inc., 2020)
"This book covers the general properties of heterocyclic compounds and methods for their preparation to use in applications of green chemistry. Heterocyclic compounds are an important class of molecules in organic chemistry due to their presence in natural products and their use in pharmaceuticals and new materials. They also play a vital role in the metabolism of living cells. Heterocyclic compounds have a wide range of applications in agrochemicals, pharmaceuticals, veterinary products, etc. This research-oriented volume, Modern Green Chemistry and Heterocyclic Compounds: Molecular Design, Synthesis, and Biological Evaluation, is ideal for readers who want to fully realize the almost limitless potential of heterocyclic compounds and to discover new and effective pharmaceuticals among heterocyclic compounds, the largest and most varied family of organic compounds. The book features several case studies and step-by-step descriptions of synthetic methods and practical techniques. It also serves as a guide for chemists, offering them new insights and new paths to explore for effective drug discovery."--
OCLC-licensed vendor bibliographic record.
Keywords: Heterocyclic compounds; Green chemistry; MEDICAL / Biochemistry; SCIENCE / General; SCIENCE / Life Sciences / Biochemistry